A simple perspective for trace copper determination: BaTiO3 nanostructures - Zeytinci, Nagehan Kubra; Zaman, Buse Tugba; Turak, Fatma; Bakirdere, Sezgin (TAYLOR & FRANCIS LTD, 2026)
A rapid and effective analytical method was developed for the determination of copper ions in environmental water samples using flame atomic absorption spectrometry (FAAS) coupled with dispersive solid-phase extraction (dSPE). BaTiO3 nanomaterials, synthesised via a simple hydrothermal technique, were employed as the adsorbent phase. Their crystalline structure, nanoscale morphology and high surface area were confirmed by X-ray diffraction (XRD) and scanning electron microscopy (SEM), supporting their strong affinity for metal ions. All experimental parameters were optimised in deionised water prior to application on real samples. The limits of detection (LOD) and quantification (LOQ) were calculated to be three and ten times the ratio of the standard deviation of the lowest concentration to the slope of the calibration curve, yielding values of 0.011 mg/kg and 0.036 mg/kg, respectively. Compared to direct FAAS analysis, the developed method achieved an 19-fold enhancement in detection power. In the assessment experiments of applicability, the method was applied to lake water samples. Matrix-matching calibration approach was used to account for matrix effects, and recovery values ranged from 81.5% to 111.2%, indicating high accuracy and reliability. These results demonstrate that the BaTiO3-based dSPE method is a sensitive, robust and practical approach for trace-level copper analysis in complex environmental matrices. The study also highlights the potential of BaTiO3 nanomaterials for future applications in the extraction and detection of other heavy metals and analytes across diverse sample types.
Keywords: Copper; BaTiO3; hydrothermal synthesis; lake water samples; FAAS; SOLID-PHASE EXTRACTION; HEAVY-METALS; FLUOROMETRIC-DETERMINATION; COLORIMETRIC DETERMINATION; LOW-COST; NANOMATERIALS; ADSORPTION; SAMPLES; MICROEXTRACTION; NANOPARTICLES; Chemistry; Environmental Sciences & Ecology